CORRELATION BETWEEN MOTOR ABILITIES OF ELITE FEMALE FOOTBALL PLAYERS - Petar Peev; Marin Gadev (Scientific Publishing House. NSA Press, 2018)
Focus of this research is the relationship between the motor abilities. The interest in this topic is dictated from the fact that there isn't enough information about it in elite female football. For the purpose of the research we made tests to define the level of development of the motor abilities of 68 elite female football players. We also made a descriptive statistics and correlation analysis and we received the following results: descriptive statistics shows that the researched indicators are highly homogeneous (in range of V% =2,67 to 5,05); the correlation between accelerative abilities and maximal sprinting abilities is moderate and positive (r= 0,634); the correlation between power abilities with explosive character and other researched abilities is moderate and negative (r= -0,430, r= -0,494, r= -0,455); the speed endurance abilities have moderate to strong and positive correlation with the accelerative and maximal sprinting abilities (r= 0,600, r= 0,809). Conclusions: 1) Improving the power abilities with explosive character creates beneficial conditions in development of the other motor abilities; 2) Improving of the speed abilities is a major component of the conditioning in female soccer; 3) The most important factor for improving the speed endurance is creating a "speed reserve".